Comparison of the results of numerical and experimental studies of the design of a radial-beam dome with triangular membrane core-shells. (February 2023) - Sabitov, Linar; Klyuev, Sergey; Undalov, Alexander; Mailyan, Levon; Klyuev, Alexander; Fediuk, Roman; Kashapov, Nail; Akhtyamova, Leysan; Khezhev, Tolya; Zagidullin, Ramil
Abstract: The article contains the methodology and results of theoretical and experimental studies of the stress–strain state of a conical radial-beam dome with triangular shell elements, including the work of a triangular shell element included in the design of a conical radial-beam dome. The work consists of three parts such a study of the stress–strain state of the elements of the dome frame with the inclusion of a steel membrane-shell in the work, the assessment of the stress–strain state of the steel membrane itself, as well as an engineering technique for calculating the triangular membrane panel of the dome. The stress–strain state of the elements of the dome and the steel membrane was analyzed based on the results of numerical (theoretical) methods using the finite element method in the Nastran software package, taking into account physical and geometric nonlinearity. Then the picture of the stress–strain state was compared with the results obtained by experimental methods on large-scale mock-ups of the structures of the radial beam dome and the membrane panel using deflection meters and strain gauge equipment (load cells and strain gauges). Further, conclusions are drawn about the reliability of the obtained research results and the correctness of the accepted hypotheses and assumptions that adequately reflect the actual operation of the structure, due to the similar values of displacements and stresses obtained by various methods. According to the results of numerical studies, zones with maximum stresses in the corners of a triangular sheet-membrane are found, in which plastic deformation is observed with the achievement of equivalent stresses equal to the yield strength of steel, which in turn is experimentally confirmed by the formation of folds in the steel sheet and residual deformations during unloading of structures. After statistical processing of the results, an engineering method was developed for calculating the normal and shear stresses in the membrane sheet, as well as the maximum deflection in the center of the membrane, depending on the load, the physical and geometric characteristics of the membrane and the flexible support contour.